Classics of librarianship : further selected readings in the history of librarianship - Thornton, John L. (John Leonard) (London : Library Association, 1957)
Biographies of famous figures in librarianship.
Includes index.
Bibliography: p. 197.
Keywords: Librarians -- Biography